Evaluating Progress towards Universal Health Coverage in Ukraine - Korzh, Oleksii (Technium Social Sciences Journal, 2020)
The healthcare system of Ukraine is characterized by low ratings, not only in terms of health outcomes, but also in terms of access to services, where one of the main obstacles is the financial problem, equity and justice, as well as the lack of implementation of measures aimed at positively stimulating the health potential of the population countries. The latest political revolution in Ukraine (2014) once again opened up the possibility of implementing a project of deep modernization of the Ukrainian state. However, at this time, we can witness the birth of an entirely new system of healthcare in Ukraine formed “from scratch”: with new priorities as well as completely new approaches and management principles. The transformation of the health care system began to develop gradually, with a focus on primary health care. Significant progress has been made over the past few years towards a human-centered model for the provision of health services. The process to build the National Health Service has started, which should fundamentally change the funding system by focusing not on beds (as was the case before) but on the principle “money follows the patient,” thereby planning to gradually transfer to insurance medicine.